2012
DOI: 10.1074/jbc.m112.415497
|View full text |Cite
|
Sign up to set email alerts
|

A Limited 4 Å Radial Displacement of the S4-S5 Linker Is Sufficient for Internal Gate Closing in Kv Channels

Abstract: Background: For Kv channels, only crystal structures for the open state are available. Results: Using LRET, we determined the movement of the S4-S5 linker during gating in KvAP channels. Conclusion: A small displacement of the S6 by only 4 Å is sufficient for closing of the Kv channels. Significance: We provide the first Kv channel closed state model based on cytosolic restraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…It has been confirmed that voltage-and lipid-controlled open and closed states are equivalent (7,11). The outermost arginines are suggested to interact with the headgroups of the surrounding phospholipids to stabilize themselves in the low dielectric membrane environment and facilitate the movement of the VSD from resting to the activated state (2,4,8,9,12,13).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…It has been confirmed that voltage-and lipid-controlled open and closed states are equivalent (7,11). The outermost arginines are suggested to interact with the headgroups of the surrounding phospholipids to stabilize themselves in the low dielectric membrane environment and facilitate the movement of the VSD from resting to the activated state (2,4,8,9,12,13).…”
mentioning
confidence: 71%
“…In POePC, the phosphate group is ethylated, whereas the phosphate has been removed in DOTAP. Primarily used for cell transfection, DOTAP has been shown to shift the voltage dependence of KvAP to more positive potentials, most likely by favoring the resting state of the VSD (4,7,11). Although DOTAP is not a phospholipid, KvAP reconstituted in pure DOTAP vesicles has been shown to adopt the native closed state conformation of the protein (7,11,16).…”
Section: Limited Exchange Of Annular Lipids Around Kvap-purifiedmentioning
confidence: 99%
“…S4 is considered the principal component of voltage sensing because it contains positively charged residues that are periodically aligned at every third position. The first four arginines (R1-R4) of S4 sense and interact with the surrounding electric field, and move the S4 outward during depolarization and inward during hyperpolarization in a combination of translation, rotation and tilt (Faure et al, 2012; Li et al, 2014a, 2014b; Vargas et al, 2012; Yarov-Yarovoy et al, 2012). These changes are mechanically transmitted to the pore domain via the S4–S5 linker and the C-terminal S6 of the same and neighboring subunit, leading to gating of the central pore (Batulan et al, 2010; Wall-Lacelle et al, 2011; Haddad and Blunck, 2011; Muroi et al, 2010; Long et al, 2005b; Catterall, 2010; Bezanilla, 2005; Lu et al, 2001, 2002; Labro et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The second fluorescence change occurs in the same direction, so it might be the S4 continuing in the same direction and might include the S4-S5 linker. The S4-S5 linker has been shown to move during gating (6). It is covalently linked to the S5 and also anneals to the C terminus of the S6, which forms the cytosolic gate of the ion-conducting pore (30,(40)(41)(42).…”
Section: C-terminal S4 Region Moves During Opening and C-type Inactivmentioning
confidence: 99%
“…1A) undergo a major conformational change upon membrane depolarization driven by the positive charges in the S4, which finally leads to opening of the pore domain (transmembrane helices S5-S6). Based on the consensus on the closed (initial) and open (final) state structures (1)(2)(3)(4)(5)(6), the gating movement has been predicted; the S4 helix is projected to slide upward and tilt with respect to the membrane normal, and this movement pushes the S4-S5 linker and the S6 helix inward and closes the ion-conducting pore. However, this projection relies on linear interpolations between the closed and open state and lacks any information on dynamics or intermediate states.…”
mentioning
confidence: 99%